Perbandingan Tingkat Penyembuhan Tulang Antara Isolated Tibial Diaphyseal Fracture, Both Tibial dan Fibula Diaphyseal Fracture Setelah Terapi Interlocking Intramedullary Solid Nail - Muhammad Rustam HN; Nina Indriyani (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2018)
ABSTRACTOne of the fixation method is interlocking intramedullary solid nail that can enhance the callus formation in tibial diaphyseal fracture through the secondary healing. The research aimed to compare the rate of bone healing between isolated tibial diaphyseal fracture and both diaphyseal tibial and fibular fracture after therapy solid interlocking intramedullary nail. This research was conducted by comparing the results of the cure rate among patients with isolated fractures of the tibia and fracture of the tibia with fractures of the fibula during November 2007 to December 2015. The first group, comprising 29 patients and the second group comprised 47 patients. All patients had solid action intramedullary nail. The evaluation was done 30 weeks post-surgery, to assess the Union Rate using Radiographic Union Score for tibial Fractures (RUST). Data were analyzed using non-parametric test of Mann-Whitney test for comparing the union rate between the two groups. The results showed that 27 of 29 patients with isolated tibial fractures had RUST score > 7 and 2 patients with RUST score < 7. Meanwhile, 44 patients out of 47 patients with both diaphyseal tibial and fibular fracture, having RUST score > 7 and 3 patients with a score < 7. Keywords: Interlocking intramedullary solid nail, Isolated Tibial Diaphyseal Fracture Radiographic Union Score, Unionrate